Changes in attitudes of consumers of sports and recreational services in the context of Covid-19 - Sowier-Kasprzyk, I.; Widawska-Stanisz, A. (Journal of Physical Education and Sport, 2020)
The article concerns the issue of the coronavirus risk and the related restrictions in relation to human physical activity. The article concerns the behavior of consumers of sports and recreational services when there is a risk of contracting COVID-19. The COVID-19 situation disrupts the normal operation of sports and recreation centers. In many cases, the freezing of the economy resulted in a loss of financial liquidity in many enterprises, including sports and recreation centers. These companies had to look for solutions how they could stay in the market and continue functioning after the unfreezing economy. After the opening of sports and recreational facilities, epidemic-related guidelines and standards have been established and must be followed by these facilities. However, the participants of physical activity do not feel fully safe using these centers, and therefore many of them stop going to them or use them less frequently than before. The article shows the situation and how the situation has changed from the beginning of the pandemic to the present day. The respondents commented on whether they use the club card, whether they use or have used online classes conducted by coaches, and whether they returned to clubs immediately after lockdown. Moreover, the research shows how women and men perceive fitness classes conducted during a pandemic. It was surprising that men and women perceived and assessed the quality of activities conducted during the pandemic differently. This is probably due to the fact that we have different needs for sports and recreational services depending on gender.